Lithium ion battery electrolyte additive and preparation method thereof

By adding free radical polymerizable electrolyte monomers, free radical initiators, heat absorbers and catalysts to the lithium-ion battery electrolyte solution, a gel layer is formed to isolate the electron passage and absorb heat, which solves the problem of thermal runaway in lithium-ion batteries under abnormal conditions, and significantly improves the safety and intrinsic safety of the battery.

CN119833758APending Publication Date: 2025-04-15WUHU ETC BATTERY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510171073.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Lithium-ion batteries may get out of control under abnormal conditions, causing a sharp increase in the internal pressure of the battery, rupture of the battery case, and leakage of the electrolyte, which will cause serious safety accidents such as fires and explosions.

Method used

A lithium-ion battery electrolyte additive is provided, including free radical polymerizable electrolyte monomers, free radical initiators, heat absorbers and catalysts. Through these components, the gel layer is formed when the temperature rises, electrons are isolated, heat is dissipated, and heat is dissipated, and thermal runaway is delayed.

Benefits of technology

It significantly improves the safety of the battery, delays the occurrence of thermal runaway, provides internal protection, improves the inherent safety of the battery, and does not affect the normal charging and discharging performance of the battery under normal working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833758A_ABST
    Figure CN119833758A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery electrolyte additive and a preparation method thereof, and relates to the technical field of battery electrolyte additives, and the lithium ion battery electrolyte additive comprises the following components by mass: 90% of a free radical polymerizable electrolyte monomer, 3% of a free radical initiator, 5% of a heat absorbent and 2% of a catalyst. The lithium ion battery has the beneficial effects that the safety is improved: the polyacrylamide gel layer is formed, so that an electronic path is effectively isolated, and the safety of the battery is remarkably improved. Thermal runaway is delayed: the gel layer can absorb and disperse heat, and thermal runaway of the battery is delayed; internal protection: compared with an external protection measure, the technology directly provides protection inside the battery, so that the intrinsic safety of the battery is improved; and the compatibility is good: the normal charge-discharge performance of the battery is not influenced by the reagent in the electrolyte under the conventional working condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery electrolyte additives, and in particular to a lithium ion battery electrolyte additive and a preparation method thereof. Background Art

[0002] As the current mainstream portable energy storage device, lithium-ion batteries have been widely used in electric vehicles, mobile communication equipment, energy storage systems and other fields. However, lithium-ion batteries may experience thermal runaway under abnormal conditions (such as overcharging, short circuit, high temperature, etc.), resulting in a sharp increase in internal pressure of the battery, rupture of the battery shell, and leakage of electrolyte. Electrolyte is an important component of lithium-ion batteries. Its leakage will not only lead to a decline in battery performance, but also may cause serious safety accidents such as fire and explosion.

[0003] At present, safety protection measures for lithium-ion batteries are mainly concentrated in battery management system (BMS), thermal management system, battery shell design, etc. Although these measures have improved the safety of batteries to a certain extent, it is still difficult to completely avoid electrolyte leakage in extreme cases such as thermal runaway and damage of the battery. Summary of the invention

[0004] The object of the present invention is to provide a lithium ion battery electrolyte additive and a preparation method thereof, so as to overcome the above-mentioned defects in the prior art.

[0005] A lithium ion battery electrolyte additive comprises the following components by mass ratio: 90% free radical polymerizable electrolyte monomer, 3% free radical initiator, 5% heat absorber and 2% catalyst.

[0006] Preferably, the free radical polymerizable electrolyte monomer is polydimethylsiloxane.

[0007] Preferably, the free radical initiator is a peroxide initiator, and the peroxide initiator is any one of dibenzoyl peroxide and diisopropylbenzene peroxide.

[0008] Preferably, the heat absorbent is methyl ammonium nitrate.

[0009] Preferably, the catalyst is N,N-methylenebisacrylamide.

[0010] The preparation method of the lithium ion battery electrolyte additive comprises the following steps:

[0011] S1. First, the ingredients are prepared in the following manner according to the mass ratio: 70% lithium ion electrolyte, 27% free radical polymerizable electrolyte monomer, 0.9% free radical initiator, 1.5% endothermic agent and 0.6% catalyst;

[0012] S2, then, adding a free radical initiator and a catalyst into the lithium ion electrolyte while stirring;

[0013] S3, then, adding the free radical polymerizable electrolyte monomer and the heat absorbent while stirring;

[0014] S4. Finally, the mixed solution is mixed with new lithium ion electrolyte in a volume ratio of 5%:95%.

[0015] The beneficial effects achieved by the present invention are:

[0016] 1. Improve safety: Through the formation of polyacrylamide gel layer, the electron path is effectively isolated, which significantly improves the safety of the battery.

[0017] 2. Delaying thermal runaway: The gel layer can absorb and disperse heat, delaying the occurrence of thermal runaway of the battery.

[0018] 3. Internal protection: Compared with external protection measures, this technology provides protection directly inside the battery, improving the intrinsic safety of the battery.

[0019] 4. Good compatibility: The reagents in the electrolyte do not affect the normal charge and discharge performance of the battery under normal working conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the gel temperature diagram under the nitrogen environment of the present invention.

[0021] Figure 2 This is a diagram of the gel temperature in an oxygen environment of the present invention.

[0022] Figure 3 This is a comparison chart of the electrochemical performance of button cells assembled with Example 1 of the present invention and type A lithium ion electrolyte.

[0023] Figure 4 This is a comparison chart of the electrochemical performance of button cells assembled with Example 2 of the present invention and type B lithium ion electrolyte.

[0024] Figure 5 It is the temperature rise curve diagram of the present invention. DETAILED DESCRIPTION

[0025] The specific implementation modes of the present invention are further explained in detail below by describing the embodiments with reference to the accompanying drawings, so as to help those skilled in the art to have a more complete, accurate and in-depth understanding of the concept and technical solution of the present invention.

[0026] The free radical polymerizable electrolyte monomer provided by the present invention is polydimethylsiloxane, which has high thermal stability, good solubility in solvents, and can form a stable gel network during polymerization; the free radical initiator is dibenzoyl peroxide, a compound that decomposes and generates free radicals at high temperature, has high thermal stability, and ensures that free radicals are decomposed and generated only when the required temperature is reached; the solvent is lithium ion electrolyte, which is used to dissolve the monomer and the initiator, and will not interfere with the formation of gel during the polymerization process. The heat absorber is methyl ammonium nitrate, which can absorb the heat generated during the gelation process; the catalyst is N,N-methylenebisacrylamide, which is used to accelerate the polymerization reaction and can also improve the conductivity of the electrolyte.

[0027] Among the additives, the free radical initiator can be a peroxide initiator, for example: diisopropylbenzene peroxide, dibenzoyl peroxide; the solvent can be a common lithium-ion battery electrolyte and the organic components therein, as long as it can dissolve the monomer and the initiator and does not interfere with the formation of the gel during the polymerization process. The type A lithium-ion electrolyte used in this application is the common Saiwei EIE series electrolyte, and the type B lithium-ion electrolyte is the common Shengge SG series electrolyte;

[0028] In normal working state, the components of free radical polymerizable electrolyte monomers, free radical initiators and other additives are stably dispersed in the basic electrolyte, and do not affect the normal charge and discharge performance of the battery; when the temperature rises to the preset threshold, the thermal initiator decomposes to produce free radicals, which trigger the cross-linking reaction of the silicone polymer. During the cross-linking process, the gel absorbs heat, thereby playing a cooling role. At the same time, oxygen in the air can accelerate the decomposition of the thermal initiator and further promote the formation of the gel.

[0029] Embodiment 1,

[0030] 1. In this embodiment, the following components are added in mass ratio: solvent (70% A lithium ion electrolyte), additives (27% polydimethylsiloxane, 0.9% dibenzoyl peroxide, 1.5% methyl ammonium nitrate, 0.6% N,N-methylenebisacrylamide)

[0031] 2.DSC test:

[0032] The electrolyte is sealed and placed in a differential scanning calorimeter (DSC): the electrolyte is heated from 25°C to 100°C at a rate of 5°C / min, and the gel time is observed. (Nitrogen environment)

[0033] The electrolyte is sealed and placed in DSC C: The electrolyte is heated from 25°C to 100°C at a rate of 5°C / min, and the gel time is observed. (Oxygen environment)

[0034] 3. Electrochemical performance test:

[0035] A conventional lithium-ion button cell assembly process was used to assemble a lithium-ion battery with a positive electrode material (lithium iron phosphate), a negative electrode material (graphite), a diaphragm (polyethylene diaphragm) and a lithium-ion electrolyte solution A to which the additive of the present invention was added. The electrochemical properties of the button cell were tested at room temperature.

[0036] 4. Safety test:

[0037] Assembled into soft pack lithium-ion batteries for safety testing:

[0038] Overcharge test: Overcharge the battery and monitor the battery cell temperature throughout the process. When the battery voltage exceeds the rated voltage at a certain temperature, check whether the temperature continues to rise. After returning to room temperature, disassemble the battery and observe whether a gel structure is formed inside.

[0039] Embodiment 2,

[0040] 1. In this embodiment, the following components are added in mass ratio: solvent (70% B lithium ion electrolyte), additives (27% polydimethylsiloxane, 0.9% dibenzoyl peroxide, 1.5% methyl ammonium nitrate, 0.6% N,N-methylenebisacrylamide)

[0041] 2.DSC test:

[0042] The electrolyte is sealed and placed in a differential scanning calorimeter (DSC): the electrolyte is heated from 25°C to 100°C at a rate of 5°C / min, and the gel time is observed. (Nitrogen environment)

[0043] The electrolyte is sealed and placed in DSC C: the electrolyte is heated from 25°C to 100°C at a rate of 5°C / min, and the gel time is observed. (Oxygen environment)

[0044] 3. Electrochemical performance test:

[0045] A conventional lithium-ion button cell assembly process was used to assemble a lithium-ion battery with a positive electrode material (lithium iron phosphate), a negative electrode material (graphite), a diaphragm (polyethylene diaphragm) and a lithium-ion electrolyte of type B to which the additive of the present invention was added. The electrochemical properties of the button cell were tested at room temperature.

[0046] 4. Safety test:

[0047] Assemble batteries and perform safety tests.

[0048] Comparative Example 1

[0049] 1. The additive of the present invention is not added, and the electrolyte uses type A lithium ion electrolyte;

[0050] 2.DSC test:

[0051] The electrolyte is sealed and placed in a differential scanning calorimeter (DSC): the electrolyte is heated from 25°C to 100°C at a rate of 5°C / min, and the gel time is observed. (Nitrogen environment)

[0052] The electrolyte is sealed and placed in DSC C: the electrolyte is heated from 25°C to 100°C at a rate of 5°C / min, and the gel time is observed. (Oxygen environment)

[0053] 3. Electrochemical performance test:

[0054] The conventional lithium-ion button cell assembly process was used to assemble the positive electrode material (lithium iron phosphate), the negative electrode material (graphite), the separator (polyethylene separator) and the lithium-ion electrolyte of type A into a lithium-ion battery. The electrochemical performance of the button cell was tested at room temperature.

[0055] 4. Safety test:

[0056] Assembled into soft pack lithium-ion batteries for safety testing:

[0057] Comparative Example 2

[0058] 1. No additives of the present invention are added, and the electrolyte uses type B lithium ion electrolyte;

[0059] 2.DSC test:

[0060] The electrolyte is sealed and placed in a differential scanning calorimeter (DSC): the electrolyte is heated from 25°C to 100°C at a rate of 5°C / min, and the gel time is observed. (Nitrogen environment)

[0061] The electrolyte is sealed and placed in DSC C: the electrolyte is heated from 25°C to 100°C at a rate of 5°C / min, and the gel time is observed. (Oxygen environment)

[0062] 3. Electrochemical performance test:

[0063] The conventional lithium-ion button cell assembly process was used to assemble the positive electrode material (lithium iron phosphate), the negative electrode material (graphite), the separator (polyethylene separator) and the lithium-ion electrolyte of type B into a lithium-ion battery. The electrochemical performance of the button cell was tested at room temperature.

[0064] 4. Safety test:

[0065] Assemble into soft-pack lithium-ion batteries for safety testing;

[0066] 1. DSC results analysis

[0067] like Figure 1 As shown, the electrolyte was heated from 25°C to 100°C in a nitrogen environment at a temperature increase rate of 5°C / min, and the gel time was observed (see Table 1):

[0068] Whether gel Gel start temperature Complete gel temperature Example 1 yes 58℃ 87℃ Example 2 yes 60℃ 88℃ Comparative Example 1 no \ \ Comparative Example 2 no \ \

[0069] Table 1

[0070] In summary, both Example 1 and Example 2 can gel, while Comparative Example 1 and Comparative Example 2 cannot gel, which indicates that the additive can cause the electrolyte to solidify after the temperature rises.

[0071] like Figure 2 As shown, the electrolyte was heated from 25°C to 80°C in an oxygen environment at a temperature increase rate of 5°C / min and maintained at 80°C to observe the gel time (see Table 2):

[0072] Whether gel Gel start temperature Complete gel temperature Example 1 yes 53℃ 80℃ Example 2 yes 54℃ 83℃ Comparative Example 1 no \ \ Comparative Example 2 no \ \

[0073] Table 2

[0074] Both Example 1 and Example 2 can gel, while Comparative Example 1 and Comparative Example 2 cannot gel. Compared with the data of nitrogen, the gelation start temperature and the full gelation temperature of oxygen are lower than those in the nitrogen environment, indicating that oxygen can accelerate the gelation process of the electrolyte.

[0075] 2. Electrochemical Performance

[0076] like Figure 3 As shown, the electrochemical performance of the button cell assembled with Example 1 and A lithium ion electrolyte is compared (see Table 3):

[0077] Charging capacity mAh / g Discharge capacity mAh / g First effect% Example 1 342.33 363.15 94.27 A lithium ion electrolyte 339.38 358.72 94.61

[0078] Table 3

[0079] like Figure 4 As shown, the electrochemical performance of the button cell assembled with Example 2 and lithium ion electrolyte B is compared (see Table 4):

[0080] Charging capacity mAh / g Discharge capacity mAh / g First effect% Example 2 342.06 362.53 94.35 B lithium ion electrolyte 342.24 362.34 94.45

[0081] Table 4

[0082] In summary, the polarization and charge-discharge capacity performance of Example 1 and electrolyte A are basically the same, and the polarization and charge-discharge capacity performance of Example 2 and electrolyte B are also basically the same. The inventive reagent does not affect the normal charge-discharge performance of the battery under normal working conditions. III. Safety test of lithium-ion batteries (see Table 5)

[0083] Overcharge test phenomenon Example 1 No burning, no explosion Example 2 No burning, no explosion Comparative Example 1 combustion Comparative Example 2 combustion

[0084] Table 5

[0085] like Figure 5As shown, after the battery temperature of the battery to which the additive of the present invention is added reaches its gel temperature, the rising speed is significantly lower than that of the battery without the additive of the present invention, and the battery to which the additive of the present invention is added does not burn or explode, thus protecting the battery integrity and effectively preventing the occurrence of internal short circuit.

[0086] The above-described embodiments of the present invention do not constitute a limitation on the protection scope of the present invention. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A lithium-ion battery electrolyte additive, characterized in that: The invention comprises the following components in weight ratio: 90% of free radical polymerizable electrolyte monomer, 3% of free radical initiator, 5% of heat absorbent and 2% of catalyst.

2. A lithium-ion battery electrolyte additive according to claim 1, characterized in that: The free radical polymerizable electrolyte monomer is polydimethylsiloxane.

3. The lithium-ion battery electrolyte additive according to claim 1, characterized in that: The free radical initiator is a peroxide initiator, and the peroxide initiator is any one of dibenzoyl peroxide and diisopropylbenzene peroxide.

4. The lithium-ion battery electrolyte additive according to claim 1, characterized in that: The heat absorbent is methyl ammonium nitrate.

5. The lithium-ion battery electrolyte additive according to claim 1, characterized in that: The catalyst is N,N-methylenebisacrylamide.

6. The method for preparing the lithium ion battery electrolyte additive according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. First, the ingredients are prepared in the following manner according to the mass ratio: 70% lithium ion electrolyte, 27% free radical polymerizable electrolyte monomer, 0.9% free radical initiator, 1.5% endothermic agent and 0.6% catalyst; S2, then, adding a free radical initiator and a catalyst into the lithium ion electrolyte while stirring; S3, then, adding the free radical polymerizable electrolyte monomer and the heat absorbent while stirring; S4. Finally, the mixed solution is mixed with new lithium ion electrolyte in a volume ratio of 5%:95%.